The absence of thrombin-like activity in Bothrops erythromelas venom is due to the deletion of the snake venom thrombin-like enzyme gene - Lotto, Nicholas P. (PLoS One, 2021)
Snake venom thrombin-like enzymes (SVTLEs) are serine proteinases that clot fibrinogen. SVTLEs are distributed mainly in venoms from snakes of the Viperidae family, comprising venomous pit viper snakes. Bothrops snakes are distributed throughout Central and South American and are responsible for most venomous snakebites. Most Bothrops snakes display thrombin-like activity in their venoms, but it has been shown that some species do not present it. In this work, to understand SVTLE polymorphism in Bothrops snake venoms, we studied individual samples from two species of medical importance in Brazil: Bothrops jararaca, distributed in Southeastern Brazil, which displays coagulant activity on plasma and fibrinogen, and Bothrops erythromelas, found in Northeastern Brazil, which lacks direct fibrinogen coagulant activity but shows plasma coagulant activity. We tested the coagulant activity of venoms and the presence of SVTLE genes by a PCR approach. The SVTLE gene structure in B. jararaca is similar to the Bothrops atrox snake, comprising five exons. We could not amplify SVTLE sequences from B. erythromelas DNA, except for a partial pseudogene. These genes underwent a positive selection in some sites, leading to an amino acid sequence diversification, mostly in exon 2. The phylogenetic tree constructed using SVTLE coding sequences confirms that they are related to the chymotrypsin/kallikrein family. Interestingly, we found a B. jararaca specimen whose venom lacked thrombin-like activity, and its gene sequence was a pseudogene with SVTLE structure, presenting nonsense and frameshift mutations. Our results indicate an association of the lack of thrombin-like activity in B. jararaca and B. erythromelas venoms with mutations and deletions of snake venom thrombin-like enzyme genes.